CRIMINAL UNDERSTANDING OF THE CONCEPT OF A DRIVER DURING DRIVER TRAINING AND SKILL TESTING - Garjānis, Māris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The determination of the driver of a vehicle has a key role to play in administrative infringement cases and criminal matters related to the violation of road trafficking rules, since the driver who committed the offence is recognised as a subject of an administrative violation or criminal offence, which is called the liability provided by the law.The concept of a driver covered by the Road Traffic Law is unclear and limits the right of the trainee to a high quality education in a safe training process within the framework of breakdown training, creating unjustified risks for the trainee or training (instructor) responsibility.As part of the study, the problem with the concept of driver will be identified and a new concept of driver will be developed.